Organization of the gravity-sensing system in zebrafish - Zhikai Liu; David G. C. Hildebrand; Joshua L. Morgan; Yizhen Jia; Nicholas Slimmon; Martha W. Bagnall (Nature Communications, 2022)
How sensory systems are organized during development remains unclear. Here, the authors used electron microscopy to examine the gravity-sensing system in zebrafish, finding that directional tuning and developmental age are organizing principles of the transformation from vestibular sensation to motor control.